KEBIASAAN MAKAN IKAN LAMPAM (Barbodes schwanenfeldii. Blkr) DI SUNGAI KAMPAR PROVINSI RIAU - Ashfi Rayhanu; Endri Junaidi; Husnah Husnah (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2004)
Study in order to know feeding behavior of Asian Barb (Barbodes schwanenfeldii, Blkr) in Kampar river, Riau Province, was carried out in July and October 2003. Study was conducted by using field survey and Laboratory Analysis. Two sampling sites in Kampar River. Desa Pulau located at the upper part of Kampar river and Desa Danau Bingkuang located at the middle part of Kampar river were chosen based on stratification method. The research showed us, that the sequence of the feeding habit of the Asian Barb in Kampar river, in July and October 2013. Concist of fitoplankton the main food with the preponderance index value of 41,57%-48,37% The complementary food which consisf plants with prefonderance index value of 31,75%-37,99%, unidentified food with prefonderance index value of 2,09%-3,17%: the zooplankton with prefonderance index value of 0,49%-1,23% and nematode with prefonderance index value of 0,14%-0,65%. Based on the sequence of the feeding habit of the Asian Barb and tha correlation between the length of the body with ratio the length of the intestine and the length of the body Asian Barb, Asian Barb in Kampar river categorized as herbivorous fish. The environmental condition in the upper and the middle of Kampar river this can still support the growth of Asian Barb.  Keywords: Asian Barb (Barbodes schwanenfeldii, Blkr), Kampar river, Indeks of Profenderance Value